Pembelajaran Matematika Dengan Strategi Writing In Perfomance Tasks (Wipt) Untuk Meningkatkan Kemampuan Menulis Matematis - junaedi, Iwan (Kreano, Jurnal Matematika Kreatif-Inovatif, 2010)
The problem of this paper is mathematical writing as a part of mathematical communication aspect that has not been developed optimally for the students. One of a teaching process to develop the students’ability in mathematical writing is Writing in Performance Tasks (WiPT) strategy. The main purpose of this paper is to investigate whether a teaching process using WiPT strategy can increase students’ability in mathematical writing. Key words: WiPT Strategy, mathematical writing, communication.